Trends and risk factors of patient falls in Korean hospitals: A five-year national reporting data analysis - Jieun Shin; Yeon-Ju Baek; Nam-Yi Kim (PLoS ONE, 2026)
Patient falls are among the most frequent and preventable patient safety incidents in hospitals, often resulting in serious injury, prolonged hospitalization, and increased medical costs. Despite the nationwide implementation of the Korea Patient Safety Reporting and Learning System (KOPS), evidence on recent fall trends and risk factors across hospital types remains limited. This study analyzed five-year national reporting data to examine temporal trends and identify predictors of harmful inpatient falls in Korea. A retrospective cross-sectional analysis was conducted using 29,607 fall-related incidents reported to KOPS between 2020 and 2024. Variables included patient demographics, hospital characteristics, medical department, incident time, and level of harm, and multinomial logistic regression was used to identify factors associated with different levels of harm severity (near miss, adverse event, and sentinel event), with near miss as the reference category. Although the proportion of falls among all patient safety incidents declined from 56.0% in 2020 to 38.9% in 2024, the absolute number of reported falls continued to increase. Older adults aged 60 years or older and female patients had significantly higher odds of harmful falls. Long-term care hospitals and large hospitals with 500 beds or more showed elevated risks, while psychiatry and critical care departments recorded the highest proportions of sentinel events. These findings indicate that inpatient falls remain a major safety concern in Korea, particularly among older women and patients in large or long-term care hospitals. Differentiated, evidence-based prevention strategies—such as technology-assisted monitoring in large hospitals and improvements in workforce and environmental conditions in long-term care settings—are needed, alongside strengthened surveillance and data-driven safety management to reduce preventable harm.